Impact in the Reduction of Complications Through a Personalized Follow-Up Strategy to Ensure Adherence to Antihypertensive Therapy - Marín, Gustavo H. (2019)
The lack in continuity of antihypertensive treatment is one of the major common causes of uncontrolled high blood pressure and increased of adverse effects and medical costs associated to this disease. The current study aimed to investigate the relationship between a personalized strategy that guarantees the adherence to antihypertensive treatment and complications related to hypertension. To do so, 586 patients hypertensive patients attending primary care institutions in La Plata Argentina, were randomly assigned either to an intervention group that had regular and periodically follow up contact to check treatment adherence or to control group. Both groups received free of charge antihypertensive medicines. The adherence was assessed with the adherence evaluation scale of Girerd. The presence of complications of hypertension disease (stroke, angina pectoris, myocardial infarct, transient ischemic attack, heart failure, kidney failure, retinopathy and death associated to this disease) were checked monthly. Among the 293 patients included in the intervention group study 98.63 % (289/293) were adherents while only 49.14% (144/293) of the control group had continuity in the therapy. Comparing complications events developed by patients belonging to Intervention vs Control group after 24 month of follow up were for overall events 19.79% vs 27.98% (p<0.001), for stoke 0.34/1.02%(pNS); angina pectoris 4.09/6.48% (p 0.004), 0.68/1.02 (pNS), TIA 0/0.34% (p NS), heart failure 4.77 /7.16% (p0.003), while hospitalization associate to primary hypertension disease was 16.04/30.3% (p<0.001)respectively. We can conclude that a personalized strategy to guarantee hypertension treatment adherence reduce the hospitalization and several complication associated to this disease.